2012
DOI: 10.1016/j.tjog.2012.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Fertility outcome of infertile women with adenomyosis treated with the combination of a conservative microsurgical technique and GnRH agonist: Long-term follow-up in a series of nine patients

Abstract: Although the combination of careful conservative surgery and GnRH agonist therapy might provide some benefits in patients with unexplained infertility and presumed severe adenomyosis, two-thirds of the patients still failed to become pregnant. The postoperative serum level of CA125 could predict the future pregnancy rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…The present results showed that all of the study patients exhibited a significant reduction in pain symptoms, menorrhagia, serum CA125 levels and uterine size after surgery. Dysmenorrhea and menorrhagia are the characteristic symptoms of adenomyosis, and directly related to the surgical efficacy of laparoscopic adenomyomectomy [ 9 , 28 , 29 ]. Serum CA125 levels are considered as a good biomarker to diagnose and monitor the therapeutic efficacy and recurrence of adenomyosis [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results showed that all of the study patients exhibited a significant reduction in pain symptoms, menorrhagia, serum CA125 levels and uterine size after surgery. Dysmenorrhea and menorrhagia are the characteristic symptoms of adenomyosis, and directly related to the surgical efficacy of laparoscopic adenomyomectomy [ 9 , 28 , 29 ]. Serum CA125 levels are considered as a good biomarker to diagnose and monitor the therapeutic efficacy and recurrence of adenomyosis [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adenomyosis is a benign gynecologic disorder characterized by the invasion of endometrial glands and stroma in the uterine myometrium, resulting in dysmenorrhea, hypermenorrhea, and infertility [ 1 ]. Although adenomyosis may be treated with several methods, such as hysterectomy, conservative surgery, drug therapy such as gonadotropin-releasing hormone agonist therapy (GnRHa), and uterine artery embolization, complete hysterectomy can thoroughly treat this disease [ 2 - 9 ]. However, total hysterectomy is not suitable for women with adenomyosis who want to preserve their uteri and/or require fertility in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy outcome after cytoreductive surgery is reported in Figure 3. This figure covers reported studies (all are case series; case reports are not included) (56)(57)(58)(59)(60)(61)(62)(63)(64) of women trying to conceive after cytoreductive surgery for AD. Some women received ART, whereas others conceived without fertility treatment.…”
Section: Cytoreductive Surgerymentioning
confidence: 99%
“…As for spontaneous pregnancies, the overall clinical pregnancy rate was very low (18.2%). However, when using GnRH-a for 24 weeks after surgery [58,59], the pooled spontaneous pregnancy rate was higher than not using adjuvant GnRH-a. There was no significant difference between pooled results with or without GnRH-a after adenomyomectomy for pregnancy rate, live birth rate, IVF pregnancy rate, or miscarriage rate.…”
Section: Different Complete Adenomyomectomy Techniques (A) Classic Tmentioning
confidence: 88%